From motherhood to mothering : the legacy of Adrienne Rich's Of woman born - O'Reilly, Andrea, 1961- (State University of New York Press, 2004)
"Of Woman Born is not only a wide-ranging, far-reaching meditation on the meaning and experience of motherhood that draws from the disciplines of anthropology, feminist theory, psychology, and literature, but it also narrates Rich's personal reflections on her experiences of mothering. Andrea O'Reilly gathers feminist scholars from diverse disciplines such as literature, women's studies, law, sociology, anthropology, creative writing, and critical theory and examines how Of Woman Born has informed and influenced the way feminist scholarship "thinks and talks" about motherhood. The contributors explore the many ways in which Rich provides the analytical tools to study and report upon the meaning and experience of motherhood."--Jacket